Stimulating the body, mind and soul in a healing setting based on biophilic design approach at Hospital Serdang, Selangor - Abdul Rashid, Muhammad Afiq (2018)
The inclusion of nature in healthcare facilities for its restorative healing benefit begins earlier in ancient age however it gradually lost in the development of the modern hospital. In Malaysia, most of the public hospital only focusing on the built environment, disregarding the green outdoor environment. There also lack of study on the implementation of healing environment through therapeutic landscape. Therapeutic garden is particularly important in promoting health and physical well-being. It brings more benefit not only to the patient, but to the staff and also the visitors. This study aims to identify the restorative design characteristics based on Common Design Recommendation tool and toward rehabilitating the outdoor environment at Hospital Serdang into a natural healing setting based on biophilic design approach. Hospital Serdang was selected due to the abundance of unutilized green area. The area was also selected due to the accessibility to all users who are mainly the patients, staff and visitors. Healing environment at Hospital Serdang is a vision of green outdoor environment at the hospital that serve to give stimulation through healing setting with the inclusion of nature in the built environment to patients, staff and visitors of Hospital Serdang. The outcome therapeutic landscape has the potential to be implement at other public hospital in Malaysia.